From Classical Texts to Digital Platforms: Reconstructing Arabic Language Pedagogy for Multidisciplinary Education Goals - Iis Susiawati; Rizka Al Fajr (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Arabic language instruction has traditionally centered on classical Islamic texts, emphasizing rote memorization, mastery of grammar (naḥw), and rhetorical eloquence (balāghah), which, while preserving linguistic authenticity, often fail to meet the evolving educational demands of the 21st century. In an age marked by rapid technological advancement and shifting pedagogical paradigms, there is a critical need to reform Arabic teaching by integrating traditional methods with digital tools and interdisciplinary approaches. This study adopts a qualitative, literature-based methodology to explore both the foundational principles of classical pedagogy and recent innovations, including learning management systems, gamification, and AI-enhanced learning technologies. Through comparative analysis, the research identifies key disjunctions and overlaps between heritage-based teaching and modern digital practices. From this synthesis, the study proposes a reconstructed pedagogical model built on four core elements: cognitive-linguistic scaffolding, digital integration, sociocultural contextualization, and multidisciplinary instruction. This integrative approach not only fosters greater student engagement but also promotes character development in line with the objectives of Islamic education (maqāṣid al-sharīʿah). Furthermore, it supports a more adaptive and culturally responsive learning environment, contributing to broader educational reform efforts aimed at holistic learning. The findings suggest that such a model is particularly well-suited to Islamic higher education contexts while also being adaptable to global academic systems. By bridging the gap between tradition and innovation, this framework offers both a theoretical and practical foundation for modernizing Arabic language pedagogy. It holds implications for curriculum development, instructional strategies, and educational policy, advocating for a future-oriented yet culturally rooted approach to language education that respects heritage while embracing necessary transformation.